Translocator Protein 18 kDa (TSPO) Deficiency Inhibits Microglial Activation and Impairs Mitochondrial Function - Yao, Rumeng; Pan, Ruiyuan; Shang, Chao; Li, Xiaoheng; Cheng, Jinbo; Xu, Jiangping; Li, Yunfeng (Frontiers in Pharmacology, 2020)
TSPO is mainly expressed in the mitochondrial outer membrane of microglia in the central nervous system, and its expression is greatly increased when microglia are activated. However, the role and mechanism of this protein in microglial activation is not well characterized. In this study, we investigated the role of TSPO in microglial activation by isolating primary microglia from TSPO knockout mice and constructing TSPO-knockdown microglial cell line. We found that TSPO deficiency significantly inhibited microglial activation induced by LPS or IL-4. Mechanistically, TSPO deficiency greatly decreased the mitochondrial membrane potential and ATP production. Moreover, an analysis of cellular energy metabolism showed that TSPO deficiency suppressed mitochondrial oxidative phosphorylation (OXPHOS) and glycolysis, resulting in microglial overall metabolic deficits. Together, our results reveal a crucial role of TSPO in microglial activation through the regulation of mitochondrial metabolism, thus providing a potential therapeutic target for neuroinflammation-related diseases of the central nervous system.